2014
DOI: 10.1111/jace.13194
|View full text |Cite
|
Sign up to set email alerts
|

Chloride‐Ion‐Stabilized Strontium Mayenite: Expansion of Versatile Material Family

Abstract: Sr‐mayenite (S12A7) incorporating Cl− ions in its crystallographic cages up to the theoretical maximum occupancy, Sr12Al14O32Cl2, is reported in our study. The addition of a stoichiometric amount of SrCl2 to the starting mixture is effective for the formation of Sr12Al14O32Cl2 with high phase purity. Almost 100% densification is achieved using spark plasma sintering (SPS). Evaporation of SrCl2 from Sr12Al14O32Cl2, which becomes significant at sintering temperatures above ~1300°C, degrades the phase purity. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Thus, one hypothesis for the sudden conductivity enhancement in the x =0 sample (S12A7) is a result of this interstitial (direct) diffusion occurring, which provides a fast ionic conduction. As described above, it is known that bulk ionic conductivity of C12A7 is sensitive to the preparation procedure as well as measurement conditions . From the viewpoint of a physicochemical analogy between C12A7 and S12A7, further optimization of S12A7 conductivity at lower temperature (<600°C) may be possible by applying a similar analogy that was efficient for improving conductivity of C12A7.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one hypothesis for the sudden conductivity enhancement in the x =0 sample (S12A7) is a result of this interstitial (direct) diffusion occurring, which provides a fast ionic conduction. As described above, it is known that bulk ionic conductivity of C12A7 is sensitive to the preparation procedure as well as measurement conditions . From the viewpoint of a physicochemical analogy between C12A7 and S12A7, further optimization of S12A7 conductivity at lower temperature (<600°C) may be possible by applying a similar analogy that was efficient for improving conductivity of C12A7.…”
Section: Resultsmentioning
confidence: 99%
“…reported that incorporation of OH − ions in C12A7 and S12A7 induces a cage distortion as a displacement of a calcium or strontium ion toward anions located at the cage . On the other hand, Cl − ‐ion‐encaged S12A7 shows no cation displacement, presumably because the ionic radius fits the cage size . From this aspect, control of cage size is anticipated to be effective as a way to incorporate a new anion with various ionic radii because stability of the accommodated ions is considered to be related with cage size.…”
Section: Introductionmentioning
confidence: 99%
“…2). From 100–150 °C, weight loss were observed by physically absorb water and dehydration reaction of crystal water in the nitrates evaporates 17 , and small endothermic peak confirmed the first citric acid decomposition below the 200 °C, where all citrate conversion after decomposition did not occurs into gaseous products due to the decomposition of nitrate under inert gas environment 18 . The brownish color of gel also confirmed the contamination of precursors by high amount of the unburned carbon 1,5,7 .…”
Section: Resultsmentioning
confidence: 97%
“…The TGA causes phase transformation through the exothermic or endothermic process in the N 2 -gas environment from 30 to 1,100°C (Figure 2). The first weight loss was about 5%, which came into view possibly because of the physical absorption and because dehydrated crystalline water in the nitrates evaporated at about 100–150°C along with decomposition of precursor nitrides (Dong et al, 2014).…”
Section: Resultsmentioning
confidence: 99%